2013
DOI: 10.1007/s12264-013-1381-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of MTHFR C677T and F2 G20210A polymorphisms on ischemic stroke

Abstract: The predisposition to stroke might involve interactive effects among variants in several genes. We tested this hypothesis by examining the influence of polymorphisms in methylenetetrahydrofolate reductase (MTHFR) (C677T) and prothrombin (F2) (G20210A) as risk factors for stroke in Morocco. The polymerase chain reaction-restriction fragment length polymorphism methods were used to analyze DNA from 91 stroke patients and 182 controls. Association between the two polymorphisms and the risk of stroke was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Twenty-three studies focusing on IS in all age groups revealed an average age ranging from 49 ± 15.2 to 67.3 ± 9.9 years old. Thus, the average age is listed in the fifth and sixth decade [13, 15–18, 20, 21, 23–28, 32–41]. However, two studies did not specify the average age of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies focusing on IS in all age groups revealed an average age ranging from 49 ± 15.2 to 67.3 ± 9.9 years old. Thus, the average age is listed in the fifth and sixth decade [13, 15–18, 20, 21, 23–28, 32–41]. However, two studies did not specify the average age of patients.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found that three MTHFR gene polymorphisms were not significantly associated with hypertension. Many genetic studies have shown that genetic variants in the MTHFR gene have been linked to CVDs, such as coronary heart disease [28,29], type 2 diabetes [30,31], ischemic stroke [32,33] and hypertension [34,35], but the clear mechanisms need to be further investigated. Markan et al [36] reported that MTHFR rs1801133 and rs1801131 alleles and the co-occurrence of rs1801133 CT/rs1801131 CC genotypes were linked to increased risk of hypertension in the Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…Водночас у цілій низці праць не було доведено прямого впливу C677T-поліморфізму на розвиток ішемічних уражень головного мозку. Такі дані, зокрема, одержано в Індії [33], Туреччині [34], Марокко [35].…”
Section: результати та їх обговоренняunclassified